The condition of exempting the air carrier from liability and insurance for it, and the position of Iraqi and Algerian law - Kamil Luaibi, Ali; Namety, Dr.Maytham (Basra studies journal, 2022)
Abstract The air carrier's guarantee of passenger safety is a legal obligation imposed on him by law, and every condition that exempts the carrier from liability, whether it is a complete or partial exemption, is considered void for violating public order. And that the agreements amending the liability of the air carrier are the agreements that regulate the effects of liability on a destination other than that regulated by law. It is divided into three sections:- The first: It includes the exemption from liability and according to the rules of civil law, it is permissible within the scope of contractual liability, except in the case of serious error or fraud. As for the scope of tort liability, it is not permissible at all. The second: It includes limiting liability, which is a condition of exemption from liability. It is permissible in contractual liability, except in cases of fraud and gross error, and is absolutely void within the scope of tort liability. Third: The emphasis on responsibility, which is absolutely permissible, as it does not include harming the weak party. The Warsaw Convention of 1929 explicitly declared invalid liability Any condition intended to exempt the air carrier from liability and to estimate a minimum level of compensation less than the limits set forth in this Agreement is null and void( Since dealing in the air and space spheres has become a necessity dictated by the current conditions of life and the presence of many risks to air transport operations and the exposure of passengers to accidents and damages, most airlines have begun to insure passengers in the air transport contract, as well as insurance on aircraft against aviation risks, as most countries of the world are obligated Air transport companies carry out insurance, and international airlines have also adopted the automatic insurance system, which is to insure passengers against damages that may befall them as a result of aviation risks, and they are authorized to obtain compensation from the insurer (insurance companies).